Delivery of IL-2 to the T Cell Surface Through Phosphatidylserine Permits Robust Expansion of CD8 T Cells - MacDonald, Alana; Lam, Brandon; Lin, John; Ferrall, Louise; Kung, Yu Jui; Tsai, Ya Chea; Wu, T.-C.; Hung, Chien-Fu (Frontiers in Immunology, 2021)
The phospholipid phosphatidylserine (PS) is naturally maintained on the cytoplasmic side of the plasma membrane. Independent of apoptosis, PS is redistributed to the surface of CD8 T cells in response to TCR-mediated activation. Annexin V (AnnV) is a protein known to bind PS with high affinity and has been effectively utilized to anchor antigen to the surface of CD8 T cells. To expand these studies, we aimed to exploit TCR activation driven PS exposure as a target to deliver cytokine, namely interleukin-2 (IL-2), to the surface of CD8+ T cells. This was accomplished using a novel chimeric fusion protein of annexin V and interleukin 2 (AnnV-IL2). In vitro analysis revealed that AnnV-IL2 is able to specifically bind PS on the T cell surface following TCR stimulation. Consequently, AnnV-IL2 proved to be significantly more effective at enhancing T cell activation compared to recombinant IL-2. In vivo, AnnV-IL2 promotes robust expansion of antigen-specific cells capable of interferon gamma (IFNγ) production when administered following peptide vaccination. Importantly, upon antigen rechallenge, AnnV-IL2 treatment mice demonstrated a stronger secondary expansion, indicating durability of AnnV-IL2 mediated responses. Our data supports the use of AnnV-IL2 to modulate antigen-specific T cell immunity and demonstrates that the PS-AnnV axis is a feasible mechanism to target diverse cargo to CD8 T cells.